The Effect of Implementing Problem-Based Learning (PBL) Model on Junior High School Students' Learning Outcomes on Cell Material - Delsarim Krisme Ina; Yulita Adelfin Lede; Oktavianus Deke; Geterudis Kerans (Equator Science Journal, 2026)
The study aims to investigate the effect of implementing the Problem Based-Learning (PBL) model on students’ learning outcomes in science subject matter, specifically cell introduction, for Grade VIII Students at SMP Gloria Dei Wee Kura. The research employed a quasi-experimental method with a Pre-test and Post-test  Control Group Design. The subject consisted of 22 students divided into two classes: 11 students in the experimental calss and 11 students in the control calss. The research instrument was a multiple-choice test consisting of 14 items that had been tested for validity and reliability. Data collection was conducted through Pre-test and Post-test, while data analysis was carried out using the non-parametric Mann-Whitney U Test with the assistance of SPSS version 16.0. The results showed a significant difference in learning outcomes beetwen the experimental class and the control class, a significance value of 0,000 < 0,05. This finding demonstrates that the application of the Problem Based-Learning (PBL) model has a positive effect on students’ learning outcomes in the science topic of Cell Introduction for Grade VIII at SMP Gloria Dei Wee Kura.